2001
DOI: 10.1034/j.1600-051x.2001.028002146.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive treatment with subantimicrobial doses of doxycycline: effects on gingival fluid collagenase activity and attachment loss in adult periodontitis

Abstract: Doxycycline administered at subantimicrobial doses led to improvements in disease parameters, with no apparent side effects, and appears to have significant potential as an oral adjunctive therapy in the long-term management of adult periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
1
11

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(185 citation statements)
references
References 38 publications
9
164
1
11
Order By: Relevance
“…Therefore modulating immunoinflammatory response to the bacterial exposure is an important concept in the treatment of various inflammatory diseases including periodontal disease (27,28). Doxycycline, a member of the tetracycline family of antibiotics, has been approved by the United States Food and Drug Administration (FDA) as a host modulatory agent for use as an adjunct to conventional therapy for the treatment of chronic periodontitis 4 (7, 29,30). Approval of doxycycline, more specifically subantimicrobial dose doxycycline was based on its ability to inhibit the activity of matrix metalloproteinases (MMPs).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore modulating immunoinflammatory response to the bacterial exposure is an important concept in the treatment of various inflammatory diseases including periodontal disease (27,28). Doxycycline, a member of the tetracycline family of antibiotics, has been approved by the United States Food and Drug Administration (FDA) as a host modulatory agent for use as an adjunct to conventional therapy for the treatment of chronic periodontitis 4 (7, 29,30). Approval of doxycycline, more specifically subantimicrobial dose doxycycline was based on its ability to inhibit the activity of matrix metalloproteinases (MMPs).…”
Section: Introductionmentioning
confidence: 99%
“…This results was agreement with the results of other studies which showed that tetracycline used in the treatment of periodontal disease have therapeutic effect unrelated to their antimicrobial activity. (16,20,39,40) Studies proposed that tetracycline, even in low dose inhibit MMPs activity and therefore, it was recommended to be used where degradation of connective tissue matrix was marked.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of metronidazole and clindamycin for three weeks also produced improved attachment levels. (Gomi, et al, 2007, Sigusch, et al, 2001. Some data to date supports a clinical benefit from the use of azithromycin as a systemic approach in combination with mechanical routines.…”
Section: Systemic Antibioticsmentioning
confidence: 99%
“…Some data to date supports a clinical benefit from the use of azithromycin as a systemic approach in combination with mechanical routines. In one limited study, seventeen subjects receiving azithromycin (500 mg), three days before full-mouth scaling and root planing produced greater clinical improvement than in seventeen subjects treated with full-mouth scaling and root planing alone (Gomi, et al, 2007). Dastoor et al studied thirty patients who reported smoking more than one pack per day and presented with periodontitis.…”
Section: Systemic Antibioticsmentioning
confidence: 99%